Identity Negotiations of Trans Women at the Indonesia-Singapore Border, Kasu Island in Batam City - Firdaus Firdaus; Sri Wahyuni; Nikodemus Niko (Randwick International of Social Science Journal, 2022)
The existence of transgender people in Indonesia is still considered a mismatch with norms in society. Not infrequently, they are individually and community marginalized, criminalized, and even persecuted. This study aims to determine the negotiation of gender identity in trans women on Kasu Island, the Indonesia-Singapore border. The existence of trans women on Kasu Island is not a new thing, but the social environment does not mind their existence. This study uses a qualitative research method of case studies. Data collection was carried out through in-depth interviews and observations. Secondary data is obtained through online searches of relevant literature. The results of this study revealed that the existence of trans women on Kasu Island faces fluid identity management and negotiations over a close social environment (attachment identity). The existence of trans women in the border areas of this country is inseparable from the influence of the modern situation in the country of Singapore.